A novel ultrawideband bandpass filter with one notch‐band and wide stopband. Issue 11 (26th August 2013) - Yang, Fan; Wei, Feng; Liu, Shu‐Fang; Shi, Xiao‐Wei
ABSTRACT A novel ultrawideband bandpass filter with one notch‐band, high selectivity, and wide stopband is investigated in this article. The basic filter is composed of two microstrip‐slot transitions with novel annular stubs, which are used to obtain the required bandwidth with high selectivity. And, a cross‐coupling between the feed lines (input and output) is introduced to broaden the stopband. In addition, a short‐circuited stepped‐impedance resonator is used to obtain one notch‐band. The simulated and experimental performances are presented in this work where good agreement is obtained. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2624–2628, 2013